Development of augmented reality as physics learning media on electric concepts. Issue 4 (March 2021) - Ismail, A; Rahayu, G; Putera, M A K; Aghniya, N N; Gumilar, S
Abstract: The 21st Century learning requires technology in the learning process, including physics learning using abstract concepts. Furthermore, many teachers do not ap-ply technology in the classroom because of the teacher's limitations in making learning media. The purpose of this research was to create an augmented reality-based learning media that can be used in classroom learning. The research method used in this research was Research and Development. The development procedure consists of a preliminary, design, development and implementation. In the preliminary study phase aims to analyse the needs of the world of education so that the direction of design and development to be made clearer and more precise. In the design and development phase, the researcher designed and created an augmented reality application and developed this augmented reality from a marker card to a real object marker. In the development stage augmented reality was judged by physicists and experts in the field of technology. After being judged, the application made was implemented and tested on 10 types of devices with different OS and implemented in classroom learning. Based on the test results, it can be concluded that the augmented reality application that has been made with successfully tested using several different devices and validated by experts and de-cleared eligible or good for use.